2019
DOI: 10.1212/wnl.0000000000007265
|View full text |Cite
|
Sign up to set email alerts
|

Community exercise is feasible for neuromuscular diseases and can improve aerobic capacity

Abstract: ObjectiveThe aim of this phase 2 trial was to ascertain the feasibility and effect of community-based aerobic exercise training for people with 2 of the more common neuromuscular diseases: Charcot-Marie-Tooth disease type 1A (CMT) and inclusion body myositis (IBM).MethodsA randomized single-blinded crossover trial design was used to compare a 12-week aerobic training program using recombinant exercise bicycles compared to a control period. The training occurred 3 times per week in community gyms local to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 25 publications
4
52
1
1
Order By: Relevance
“…In line with our findings of improvement in MMT-8, outcome measures assessing muscle strength improved to a different extent also in other mentioned studies, including MMT-8 in [ 37 , 40 ], voluntary repetition maximum (VRM) in [ 40 , 41 ], peak isometric torque (PIT) in [ 41 , 48 ], leg press and/or leg extension and/or bench press in [ 42 , 43 , 51 ], or dynamometry of both distal and proximal muscles in [ 45 ]. Contrary to our study, no improvement in muscle strength was found according to MMT-8 in [ 39 , 44 , 49 , 51 ], MMT on a scale from 0 to 20 in [ 48 ], or PIT in [ 50 ]. Similar to our findings, muscle endurance improved to a varying extent in four studies by Alexanderson et al, assessing FI-2 with improvement only in shoulder flexion in [ 44 ] or FI in [ 38 , 46 , 47 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with our findings of improvement in MMT-8, outcome measures assessing muscle strength improved to a different extent also in other mentioned studies, including MMT-8 in [ 37 , 40 ], voluntary repetition maximum (VRM) in [ 40 , 41 ], peak isometric torque (PIT) in [ 41 , 48 ], leg press and/or leg extension and/or bench press in [ 42 , 43 , 51 ], or dynamometry of both distal and proximal muscles in [ 45 ]. Contrary to our study, no improvement in muscle strength was found according to MMT-8 in [ 39 , 44 , 49 , 51 ], MMT on a scale from 0 to 20 in [ 48 ], or PIT in [ 50 ]. Similar to our findings, muscle endurance improved to a varying extent in four studies by Alexanderson et al, assessing FI-2 with improvement only in shoulder flexion in [ 44 ] or FI in [ 38 , 46 , 47 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We believe that the significant mitigation of depression observed in our study is secondary to the functional improvement and sustained motivation thanks to the physiotherapist. In line with our findings, no significant change in perceived exertion or muscle pain during the intervention was found in four studies [ 39 , 44 , 45 , 50 ]. Similarly, no increase in either one or several systemic markers of muscle damage or inflammation (mostly CK, LD, CRP, or ESR) was detected in any of the 15 above-mentioned studies [ 37 51 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A significant increase in peak oxygen uptake (VO 2 max) (mean 1.5 L/min ± SE 0.2 before the programme to 2.1 L/min ± 0.3 after, p G 0.05) was observed, as well as mean strength on hip abduction (16.6%), shoulder abduction (39.8%), hip flexion (35.6%), and knee flexion (10.5%, all p G 0.05) post-exercise programme. Some findings were replicated in a prospective randomized single-blinded crossover trial [26], where 17 IBM participants undertook a 12-week aerobic exercise programme, showing a large increase in VO 2 max (1.72 on Cohen d analysis ± SD 0.28, and 1.68 on Hedges g analysis ± SD 0.42).…”
Section: Exercisementioning
confidence: 85%
“…In fact, a subset of dermatomyositis and polymyositis patients undergoing resistance training showed decreased disease activity [ 90 ]. A recent randomized, single-blinded crossover trial examining aerobic training with exercise bicycles showed safety and improved aerobic capacity in patients with inclusion body myositis, providing class II evidence for aerobic training improving cardiopulmonary fitness [ 91 ]. We recommend combined aerobic and strength training [ 86 ], with avoidance of high-impact and eccentric exercises.…”
Section: Physical/speech Therapy and Exercisementioning
confidence: 99%